IMPLEMENTATION OF HUMAN RIGHTS VALUES AND CRIMINAL PROCEDURE LAW AS A FORM OF PROTECTION FOR SUSPECTED, DEFENDANTS, AND DEFENDANTS (International Journal of Cultural and Social Science, 2026)
This study aims to examine the implementation of human rights values within criminal procedural law as a form of protection for suspects, alleged offenders, and defendants. The main issue addressed is the gap between legal norms that guarantee human rights protection and law enforcement practices that still demonstrate violations, particularly at the investigation stage. This research employs a normative legal method with statutory, conceptual, and case approaches, supported by library research as the data collection technique. The findings indicate that, normatively, Indonesia’s criminal procedural law has accommodated fundamental human rights principles, such as the presumption of innocence, the right to legal counsel, and the prohibition of torture. However, in practice, violations persist due to ambiguous legal provisions, weak accountability of law enforcement officials, and the dominance of a repressive paradigm within legal culture. The novelty of this research lies in the formulation of a reconstructive approach to criminal procedural law as an integrative human rights protection system through strengthening the aspects of legal substance, structure, and culture. This study concludes that comprehensive reform of criminal procedural law is necessary to achieve a fair and substantively just criminal justice system.